1996
DOI: 10.1144/gsl.sp.1996.099.01.13
|View full text |Cite
|
Sign up to set email alerts
|

The growth of normal faults by segment linkage

Abstract: Fault growth is widely described using a scaling law between maximum displacement ( D ) and length ( L ), of the form D = cL n . This expression defines a model of fault growth by radial propagation from a single seed fracture or fault. This paper presents geometrical and kinematic evidence from a set of exceptionally well exposed normal faults in Utah for an alternative mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
72
1
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 42 publications
9
72
1
1
Order By: Relevance
“…This study has demonstrated successfully that relay ramps represent conduits for fluid flow, which has been suggested previously by several authors (Peacock & Sanderson 1991;Peacock & Sanderson 1994;Trudgill & Cartwright 1994;Childs et al 1995;Cartwright et al 1996;McGill et al 2000;Imber et al 2004;Hus et al 2006, amongst others). Although some works exist that have documented fluid flow across relay ramps (Bense & Baalen 2004;Micarelli et al 2006), the effects of fault damage in relay ramps has not been quantified to date in the existing literature.…”
Section: Discussionsupporting
confidence: 82%
“…This study has demonstrated successfully that relay ramps represent conduits for fluid flow, which has been suggested previously by several authors (Peacock & Sanderson 1991;Peacock & Sanderson 1994;Trudgill & Cartwright 1994;Childs et al 1995;Cartwright et al 1996;McGill et al 2000;Imber et al 2004;Hus et al 2006, amongst others). Although some works exist that have documented fluid flow across relay ramps (Bense & Baalen 2004;Micarelli et al 2006), the effects of fault damage in relay ramps has not been quantified to date in the existing literature.…”
Section: Discussionsupporting
confidence: 82%
“…The information contained in Fig. 2 reinforces the results of other recent studies which have noted different fault architecture associated with fault segment structures or domains (Cartwright et al 1996), relay zones (Peacock & Sanderson 1994), and tip zones (McGrath & Davison 1995). It is also clear that attribute mapping from high-quality 3D seismic surveys offers an important direction for the future characterization of fault segment and damage zone geometries (see Jones & Knipe 1996).…”
Section: Fault Zone Mapping Geometry and Evolutionsupporting
confidence: 86%
“…An ideal self-similar growth is rarely observed; in general, there is a lot of scatter in throw or heave vs. length correlation plots, which is caused by the process of segment linkage (Cartwright et al, 1996;Mansfield and Cartwright, 2001), and partly also due to the use of throw and heave values rather than the real displacement. Because of strong differences in real displacement, vertical and horizontal displacement, and even throw and heave of mature, high undulated faults, it is necessary to use real displacement values as they represent the true movement along the fault.…”
Section: Implications For Fault Drag Scaling Fracture Prediction Amentioning
confidence: 99%